Castleman Disease in the Pediatric Neck: A Literature Review. Issue 6 (4th March 2013) - Rabinowitz, Mindy R.; Levi, Jessica; Conard, Katrina; Shah, Udayan K.
Abstract : Objective: To investigate the common features of cervical pediatric Castleman disease. Data Sources: Literature review of pediatric patients with cervical Castleman disease. Review Methods: Online medical journal databases were searched for patients aged 18 years or younger. Eighteen published studies were found, comprising 29 patients. Conclusions: An asymptomatic or slowly enlarging neck mass was the most common presentation. No sex differences were noted. Magnetic resonance imaging demonstrates a homogeneous, isointense to slightly hyperintense T1‐weighted signal and high signal intensity on T2‐weighted imaging. Lymphoma was the most common differential diagnosis. All patients were treated with complete surgical excision and diagnosed as hyaline‐vascular type on histology, except for 1 patient for whom histologic type was not reported. No reports of multicentric disease, plasma cell, or mixed histology were found. No recurrences were reported. Implications for Practice: In this article, we provide the largest known literature review of pediatric patients with cervical Castleman disease. Although Castleman disease is rare, it should be considered on the differential for a pediatric neck mass, particularly when presenting with an asymptomatic posterior neck mass and equivocal workup. Fortunately, our study suggests that if diagnosed as Castleman disease, the most likely diagnosis is hyaline‐vascular type, for which the long‐term prognosis is good. Surgical excision is both diagnostic and therapeutic.